Kompensasi dan Penempatan Pengaruhnya Terhadap Kepuasan Kerja Karyawan - Moh Farhan Ooktafian; Meimoon Ibrahim; Olfin Ishak; Wahyudin Hasan; Anggita Permata Yakup (Dinamis : Journal of Islamic Management and Bussiness, 2023)
The purpose of this study was to identify and analyze partially and simultaneously the independent variables of compensation and placement on the dependent variable of employee job satisfaction at PT. Batam Aero Technic. The method of analysis uses: multiple linear regression analysis, 2 independent variables and 1 dependent variable. Research results: 1) Compensation has a significance value of 0.010 1.694 it can be concluded that H1 is accepted. This means that compensation has a positive and significant effect partially on employee job satisfaction at PT. Batam Aero Technic. 2) Placement has a significance value of 0.019 1.694 it can be concluded that H1 is accepted. This means that placement has a positive and significant effect partially on employee job satisfaction at PT. Batam Aero Technic. 3) The results of the F test show that the joint effect of all independent variables of compensation (X1) and placement (X2) on the dependent variable (employee job satisfaction) shows positive and significant results at PT. Batam Aero Technic.